2021
DOI: 10.1016/j.jcf.2020.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The fungal airway microbiome in cystic fibrosis and non-cystic fibrosis bronchiectasis

Abstract: Background: The prevalence of fungal disease in cystic fibrosis (CF) and non-CF bronchiectasis is increasing and the clinical spectrum is widening. Poor sensitivity and a lack of standard diagnostic criteria renders interpretation of culture results challenging. In order to develop effective management strategies, a more accurate and comprehensive understanding of the airways fungal microbiome is required. The study aimed to use DNA sequences from sputum to assess the load and diversity of fungi in adults with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 34 publications
5
53
0
Order By: Relevance
“…60,61 Comparing mycobiome composition between CF and non-CF bronchiectasis, Cuthbertson et al (2020) reported lower diversity with increased fungal burden in CF, with a predominance of Candida in both groups. 62,63 In general, respiratory microbiome studies report that sputum has greater resemblance to that of the upper airway while BAL better represents the lower airway, however, this does not appear the case in bronchiectasis. Limited variability is observed in profiles obtained by sputum and BAL, respectively, in microbial richness, diversity and abundance.…”
Section: Specimen Type and Microbiome Composition In Bronchiectasismentioning
confidence: 99%
“…60,61 Comparing mycobiome composition between CF and non-CF bronchiectasis, Cuthbertson et al (2020) reported lower diversity with increased fungal burden in CF, with a predominance of Candida in both groups. 62,63 In general, respiratory microbiome studies report that sputum has greater resemblance to that of the upper airway while BAL better represents the lower airway, however, this does not appear the case in bronchiectasis. Limited variability is observed in profiles obtained by sputum and BAL, respectively, in microbial richness, diversity and abundance.…”
Section: Specimen Type and Microbiome Composition In Bronchiectasismentioning
confidence: 99%
“…Last, an important caveat to most of the microbiome studies published so far is the strong focus on bacteria; most reports have overlooked the presence of fungi and viruses and their impact on CF airway disease ( 26 , 43 , 44 ). Taken together, these multiple lines of evidence now make it clear that chronic CF lung infections are not restricted to bacteria and that interkingdom interactions involving viruses and fungi have the potential to be major players in CF lung disease.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Members of this family, most frequently found in NCFB, are Mycobacterium avium complex and Mycobacterium abscessus [ 57 ]. Aspergillus [ 58 ], and Candida [ 59 ] are fungi commonly identified in the respiratory secretions of NCFB patients [ 59 , 60 ]. It can be difficult to determine if these organisms play a pathophysiological role in infectious symptoms or if they are simply bystander organisms in patients with other primary pathogens.…”
Section: The Role Of Pseudomonas Aeruginosa Andmentioning
confidence: 99%